Estimating risk to ice-breeding pinnipeds from shipping in Arctic and sub-Arctic seas. (January 2020) - Wilson, Susan C.; Crawford, Imogen; Trukhanova, Irina; Dmitrieva, Lilia; Goodman, Simon J.
Abstract: Industrial shipping activity in some Arctic and sub-Arctic seas is increasing during the winter and spring seasons of heavy ice cover. Here, following from a previous study of icebreaker impact on seals in the Caspian Sea, the extent of overlap between shipping and breeding habitat of ice-associated pinnipeds in other seas is investigated. Significant industrial shipping activity in potential pinniped breeding areas during the spring pupping period 2017 was recorded in the Baltic Gulfs of Finland and Bothnia (grey and ringed seals), the White Sea and Newfoundland Belle Isle Strait (harp seal), the Ob Estuary in the Kara Sea (ringed seal), The Pechora Sea (walrus) and Sakhalin Island area in the Okhotsk sea (ringed, bearded, ribbon and spotted seals). Most areas lack sufficient pup density distribution data to apply quantitative evaluations, but for the Caspian and White Seas it was possible to estimate a measure of vessel disturbance in terms of the potential number of collisions with pups in the path of a single vessel of a given beam width, giving a result of 9.6% of Caspian seal pups and 1.9% of White Sea harp seal pups in the 2006 and 2009 seasons respectively. This study highlights the need to consider policy and regulatory frameworks for vessels transiting pinniped ice breeding areas in advance of further growth in vessel traffic during winter and spring. Stakeholders operating shipping through pinniped breeding habitat in sea ice could play a role in generating the data necessary for such impact assessments and evidence-based mitigation measures. Highlights: Shipping impact on pinnipeds pupping on sea ice has yet to be widely recognised. This study presents data on industrial vessels transiting pinniped pupping sea ice. Eight sea areas were identified with significant shipping in pupping ice. Pinnipeds at risk from ice-breaking ships included walrus and seven seal species. Potential collision risk was assessed for White Sea harp seals and Caspian seals.